Psychological Review: The Development of Children's Religion and Its Influencing Factors - Zahra Alifah; Eva Latipah; Muhimmatun Nailatul Aliyah; Wildani Ibda Nazihah; Dani Daffa Priyolaksono (Insight School Academy, 2025)
Introduction to The Problem: The development of religion occurs significantly in children, making it important for parents and educators to understand children's religious development. Purpose: This study aims to examine children's religious development from a developmental psychology perspective. Design/methods/ approach: This study is a quantitative study using a library research method. Data were collected from various written sources, including digital academic databases, and then analyzed using data triangulation and content analysis. Findings: The results of this study show that child development is influenced by both internal factors, including heredity and personality, and external factors, such as the family, school, and community environment. There are three theories of religious spiritual growth in children, including dependency theory, religious instinct theory, and fitrah theory. Furthermore, the stages of child development are divided based on Ernest Harms’s views, including the fairy tale stage, the reality stage, and the individual stage. In addition, Imam Bawani divides the phases of children's religious development into the phase in the womb, the baby phase, the childhood phase, and the school phase. This study indicates that parents and the environment have a crucial role in shaping children's faith from an early age.